Penatalaksanaan Kompres Air Hangat Terhadap Penurunan Suhu Tubuh pada Asuhan Keperawatan Anak dengan Demam Berdarah Dengue (DBD) - Sari Octarina Piko; Rian Marhta; Rifka Zalila; Dira Frisca Fremista; Tuti Elyta (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by a severe dengue virus characterized by sudden fever, bleeding, and plasma leakage as evidenced by a decrease in the number of platelets, an increase in hematocrit, the presence of pleural effusion accompanied by a decrease in albumin, protein, and sodium levels (Suroso, 1984 in Nisa et al., 2013). The purpose of this study was to find out the description of giving warm water compresses to decreasing body temperature in dengue hemorrhagic fever (DHF). The design of this research is descriptive with the case study method. Management of Dengue Hemorrhagic Fever (DHF), namely the administration of warm water compresses to reduce body temperature which was carried out at Bhayangkara M. Hasan Hospital Palembang from 15 May 2023 to 17 May 2023. The subjects of this study were 2 patients with Dengue Hemorrhagic Fever (DHF). . The plan given is the Provision of Warm Water Compresses for Lowering Body Temperature in Dengue Hemorrhagic Fever (DHF). The research instruments used were nursing care formats, medical records, thermometers, nierbeken, warm water (43-46°C), washcloths and varnish. After giving warm water compresses for 3 days, the two patients experienced a decrease in body temperature. Body temperature on An